Road users perception towards Automated Enforcement System (AES) at South Kelang Valley Expressway (SKVE) / Muhammad Faiz Shoaib and Muhammad Hafizi Harith - Shoaib, Muhammad Faiz; Harith, Muhammad Hafizi (Faculty of Administrative Science and Policy Studies, 2014)
The study emphasize on the road users perception toward the Automated Enforcement System (AES) at South Kelang Valley Expressway (SKVE). Automated Enforcement System (AES) is the road safety enforcement system to improve traffic enforcement at Malaysia. Automated Enforcement System (AES) is the road safety enforcement system to monitor all federal roads, highways and expressways. Electronic enforcement system has been applied in 90 countries around the world. Automated Enforcement System (AES) is able to automatically detect and record any traffic offenses as soon as they violate traffic law where the system is installed. Automated Enforcement System (AES) operation covers offenses such as beating the traffic light and speeding. Information of these offenses is then sent in real time online to the Automated Enforcement System (AES) Control Centre. The information is processed to identify the driver or owner of the vehicle based on the information in the database. Summons will be issued automatically and sent by mail to the traffic offenders. The system automatically sends the information to the court for trial if the traffic offenders chose not to pay the compound or decided to go for trial. (Road Transport Department, 2013)